Is education income-equalizing? Evidence from Peru - Adolfo Figueroa (CEPAL Review, 2010)
Is the education system income-equalizing? The evidence from developing countries shows that while education has expanded tremendously in recent decades, income distribution has not become more equal. This article seeks to resolve this seeming paradox. A theoretical model is constructed for the relationship between education and income in which ethnicity plays a key role in the distribution process. The model predicts that the education system is not income-equalizing. A broader set of predictions are derived from the theoretical model and then compared to Peruvian data. Statistical tests produce results that are consistent with the model’s predictions.